"Oh God! Why Did You Let Me Have This Disability?": Religion, Spirituality and Disability in Three African countries. (2nd January 2020) - Mugeere, Anthony Buyinza; Omona, Julius; State, Andrew Ellias; Shakespeare, Tom
Abstract: The discourse on the place of religion and spirituality in most peoples' lives not only conjures a multiplicity of perspectives in understanding how humanity relates to God but also lies at the core of the way many of us define success or failure. For persons living with varying forms of disability, religiosity and spirituality are two of the tightly fused core philosophies that give meaning to their lives. This paper explores the role of religious belief and affiliation for persons living with disability in Kenya, Uganda and Zambia. Based on 103 qualitative research interviews with such individuals, the study shows that persons living with disability attach a lot of importance to having faith or believing in a supreme being which gives them the strength to keep going and make sense of the events in their lives especially when they are swimming against the tide of challenges. The paper concludes that most of these individuals attribute their success not to their power, might or wisdom but to the grace of God who does not need human might or skill of fitness to accomplish His work.